Political Ideology and Tax Competition: Experimental Evidence - Eckhard Janeba (Verein für Socialpolitik, 2010)
This paper analyzes tax competition theory in an experimental setting. Economically trained students act as government and must select a labor and a capital tax rate to fund a public good, both in closed and open economy settings. Several results emerge: i) There is only weak evidence that better students choose labor tax rates closer to their (Nash) optima. ii) Tax rates on capital fall when capital becomes mobile, but much less so than theory predicts. iii) In the open economy female students choose about 9 percentage points higher tax rates on capital than male students. iv) Political ideology influences capital tax rate choices in the open economy when subjects are matched on the basis of party preference, but not when randomly matched. With political preference matching left leaning students choose about 8 percentage points higher tax rates on capital than right of center students, even though rational behavior predicts no relevance for political ideology.
Keywords: D78; H21; H73; 330; Tax Competition; Political Preference; Experiment